ALK7 Knockdown Plays a Protective Role on HG-Stimulated MCs through Activation of the Nrf2/HO-1 Pathway. (26th September 2022) - Gao, Shan; Wu, Guifu; Li, Hui; Qiao, Yuan; Dong, Chunping
Abstract : Objective . Activin receptor-like kinase 7 (ALK7) is a member of the ALK family that has a key role in diabetes. However, the role of ALK7 in diabetic nephropathy (DN) remains unclear. Methods . Herein, we evaluated the effects of ALK7 on mesangial cells (MCs). MCs were transfected with si-ALK7 or pcDNA3.0-ALK7, and then stimulated with 40 mM glucose for 24 h. Cell proliferation was detected by MTT assay. Relative ROS level was detected using DCFH-DA staining. The contents of inflammatory cytokines were determined by ELISA. Western blot analysis was used to determine the expression levels of FN, Col IV, Nrf2, and HO-1 in MCs. Results . Our results showed that ALK7 expression was induced by HG in MCs. Knockdown of ALK7 inhibited HG-induced cell proliferation. The HG-induced ROS was mitigated by si-ALK7 with decreased ROS level and NOX activity. In addition, ALK7 knockdown exhibited anti-inflammatory activity in HG-stimulated MCs. Moreover, ALK7 knockdown attenuated fibronectin (FN) and collagen IV (Col IV) expression in MCs. Knockdown of ALK7 enhanced Nrf2/HO-1 pathway in MCs. Inhibition of Nrf2 reversed the protective effects of ALK7 knockdown on HG-stimulated MCs. Conclusion . ALK7 knockdown exerted protective effects on HG-stimulated MCs through activation of the Nrf2/HO-1 pathway. Thus, targeting ALK7 might be a therapeutic approach for the treatment of DN.